2015
DOI: 10.1371/journal.pgen.1005669
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Identification of Long Non-coding RNAs in Purified Cell Types from the Brain Reveals Functional LncRNA in OPC Fate Determination

Abstract: Long non-coding RNAs (lncRNAs) (> 200 bp) play crucial roles in transcriptional regulation during numerous biological processes. However, it is challenging to comprehensively identify lncRNAs, because they are often expressed at low levels and with more cell-type specificity than are protein-coding genes. In the present study, we performed ab initio transcriptome reconstruction using eight purified cell populations from mouse cortex and detected more than 5000 lncRNAs. Predicting the functions of lncRNAs using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 70 publications
(109 reference statements)
2
83
0
Order By: Relevance
“…To this collection, we added RNA sequencing data from purchased primary neural stem cells (NSCs), that were isolated from embryonic mouse cortex (E14.5) (GEO accession number GSE74643)42. The SCI data was reported by Chen et al 44.…”
Section: Methodsmentioning
confidence: 99%
“…To this collection, we added RNA sequencing data from purchased primary neural stem cells (NSCs), that were isolated from embryonic mouse cortex (E14.5) (GEO accession number GSE74643)42. The SCI data was reported by Chen et al 44.…”
Section: Methodsmentioning
confidence: 99%
“…Although studies have shown expression of lncRNAs during CNS development (Mercer et al, 2010; Ramos et al, 2013) and in OPCs (Dong et al, 2015), a mechanistic understanding of the functions of lncRNAs in myelinogenesis in the CNS remains elusive. Identification and characterization of lncRNAs during OL lineage progression are vital to our full understanding of the mechanisms of myelinogenesis and myelin repair in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The stringency of the Benjamini and Hochberg false discovery rate test likely accounts for why only one of the NATs examined met statistical significance. Although only a portion of lncRNAs that were significantly altered by drugs of abuse were NATs in the above studies, it is important to note that many NATs are expressed at low levels and in a cell type-specific manner (Cabili et al , 2011; Derrien et al , 2012; Li et al , 2013; Dong et al , 2015). Thus, small changes in expression that are observed in tissue homogenate may have functional importance in specific cell types.…”
Section: Discussionmentioning
confidence: 97%